Pendidikan Kesehatan tentang Remaja Sehat pada Adaptasi Kehidupan Baru di Kota Jambi - Mila Triana Sari; Nel Efni (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
The adolescence was a transition period from childhood to adulthood, which has many challenges from themselves or the environment, especially during the adaptation to a new life (New Normal). The Central Bureau of Statistics (2018) released the number of teenagers in Jambi province as 17.9% of the total population. If adolescents do not have the ability to face these challenges, it can have an impact on their personal health. The purpose of this activity is to increase adolescent knowledge regarding the adaptation of a new life. The activities carried out were in the form of health education using social media and power point slides. The result of this activity was an increase in adolescent knowledge about new life adaptations seen from the difference between the pre-test and post-test mean of 35.3%. In conclusion, health education for adolescents is effective in increasing the knowledge and abilities of adolescents, especially regarding new life adaptations, therefore it is hoped that health workers will regularly provide health education and mentoring to adolescents, directly by following health protocols or using various social media